The world is what it is the authorized biography of V.S. Naipaul - French, Patrick 1966- (Picador, 2009)
With great feeling for Naipaul's formidable body of work, French has produced a luminous account of the most compelling literary figure of the last 50 years. He describes how depression struck with great force, and the ways in which Naipaul's first wife helped him to cope with his double exile.